THE PHYSIOTHERAPIST IN THE PROCESS OF EDUCATION FOR CHANGE IN BEHAVIOR: THE SCHOOL BACKPACK AS A RISK FACTOR FOR POSTURAL PROBLEMS IN STUDENTS FROM THE FUNDAMENTAL EDUCATIOIN I OF THE PRIVATE NETWORK, IN THE OSASCO MUNICIPALITY, SÃO PAULO (S. P.), BRAZIL, (Fiep Bulletin - online, 2013)
With the beginning of the school year, the concerns of the parents/guardians on the purchase of materials and school backpack began. They satisfy the wishes of the child regarding the color and the pattern that are on fashion and do not know that the most important aspect is not part of their list of concerns, i.e, the vertebral column. OBJECTIVE: To verify the level of knowledge of the parents/guardians with regard to the recommended weight of the school backpack used by their children, as well as the validation of an educative material for the prevention of postural problems due to the school backpack. MATERIALS AND METHOD: The study is of the descriptive and transversal type and was carried out in an educational institution of the private network in the Osasco municipality (S.P.). The sample is composed by forty (n=40) parents/guardians of students from the 1st to the 4th series. They had replyed to a questionnaire with objective questions, which have been taken as variables. After compiled, the data have been presented in graphics and tables of simple frequency and expressed in numbers and percentages. The ethical and legal aspects have been observed. RESULTS: It has been observed that 42.50% of the parents/guardians tell that the children choose themselves the school backpack and the criterion adopted by 45,00% is the patern; 67.50% believe that the trolley school backpack is the most suitable type but 55.00% tell that their children use the school backpack with two suspenders on the back; 82.50% are unaware of the existence of the “recommended weight” or the Law of school backpack (Law Nº 2772/97) and 97.50% consider the information in the educative material (folder) very important. CONCLUSION: The results suggest high level of unfamiliarity of the parents/guardians with regard to the types of school backpack as well as the problems caused by them. The educative folder was considered valid as material for acquisition of knowledge and awareness and by its importance, since certain information are not available to the population, what makes the physiotherapist a competent professional in the promotion and protection of the health
Keywords: School Backpack; Postural Problems; Preventive Physiotherapy